Littérature française et savoirs biologiques au XIXe siècle - Klinkert, Thomas; Séginger, Gisèle (MIMESIS, 2020)
By the metaphorical power and the modelling power which they take, biological knowledge and its representations arouse in the XIXth century the fascination of the writers. They find there the source of new poetry, of an imaginary going beyond the positivist logic, but also of new textual forms, a poetics, even esthetics allowing to redefine the idea of ​​the "beautiful". This volume studies the impact of biological knowledge on literary creation in the 19th century, with three objectives: (1) studying the dissemination and reception of biological knowledge by 19th-century writers, paying particular attention to the work major foreigners in the matter; (2) analyze the use and functions of biological knowledge in literary texts, their transformations in terms of content, writing and poetics, which also presupposes the identification of the ideological issues of this knowledge; (3) think about the relationships or the discrepancies between the history of science and the history of literature, which sometimes reflects current debates, sometimes, on the contrary, is inscribed in older knowledge.